Management Of Non-Tax State Revenue At The Office Of The Port Master And Port Authority Of Class II Patimban For The 2023 Budget Period - Rahmadhani, Wahyu Agung; Hawa, Bilqis Bani; Samsudin, Udin (Doktoral Ilmu Manajemen, Universitas Pasundan, 2025)
This study discusses the management of Non-Tax State Revenue at the Patimban Class II Harbormaster and Port Authority Office in the 2023 budget period. Non-Tax State Revenue is an important source of state revenue that needs to be managed efficiently, transparently, and accountably. This study uses a qualitative-descriptive method by collecting data through in-depth interviews, direct observation, and analysis of related documents. The results show that the management of Non-Tax State Revenue at the Patimban Class II Harbormaster and Port Authority Office is supported by various digital applications such as INAPORTNET, SIMKAPEL, SIMLALA, SIMPONI, Hubla Data Center, and SAKTI, which play a role in ensuring efficiency, transparency, and accountability in the management of Non-Tax State Revenue. However, this study also identifies several challenges, including data compatibility between systems and the need to increase human resource capacity to support more optimal management.